Elevated Serum Total Bilirubin Level Is Associated with Poor Outcomes in Pediatric Patients with Sepsis-Associated Liver Injury - Yun Cui; Yijun Shan; Rongxin Chen; Chunxia Wang; Yucai Zhang (Canadian Journal of Infectious Diseases and Medical Microbiology)
Aims. The aim of this study was to assess the prognostic value of the serum total bilirubin (TBIL) level in pediatric patients with sepsis-associated liver injury (SALI). Methods. We performed a retrospective study of patients with SALI admitted to the pediatric intensive care unit (PICU) in Shanghai Children’s Hospital between December 2012 and December 2015. Serum TBIL concentration was determined within 72 h after PICU admission. Results. Seventy-two patients with SALI were included in this study. The overall mortality rate was 36.1% (26/72). The serum levels of TBIL of patients were significantly higher in the nonsurvivor group than the survivor group. Cox regression analysis indicated that the elevated serum TBIL level within 72 hours after admission was an independent risk factor of mortality in patients with SALI. Furthermore, the area under the receiver-operating characteristic (ROC) curve (AUC) for TBIL was 0.736 (95% confidence interval (CI): 0.614–0.858, P=0.001), in which the optimal cut-off value was 64.5 μmol/L. The combined index named “TBIL” and “TBA” showed an AUC of 0.745 (0.626–0.865) for predicting the prognosis in patients with SALI. In addition, the Kaplan–Meier curve indicated that the 28-day survival rate was significantly lower in patients with higher serum TBIL levels (≥64.5 μmol/L) or higher value of TBIL and TBA (≥−0.8902). Conclusions. Elevated serum TBIL level is associated with poor outcomes in pediatric SALI.